Motivation Of Students and The Use of Technologies in The Educational Process (Texas Journal of Multidisciplinary Studies, 2021)
This article describes how to motivate students in the learning process and explains that motivation is an important factor. In particular, it was noted that motivation can make a significant difference in the lives of students, laying the foundation for them to become good people in the future. It was noted that it is important to hold various events as part of the Science Month, encourage students to actively participate and reward them with honorary diplomas